2019
DOI: 10.12693/aphyspola.135.800
|View full text |Cite
|
Sign up to set email alerts
|

Property Improvement of Subzero/Cryogenic Heat Treated Camshafts made of 8620H, 16MnCr5 and 100Cr6 Steels

Abstract: Several types of camshafts that made of 8620H, 16MnCr5 and 100Cr6 steel were subzero/cryogenic heat treated and the effect of these heat treatment parameters such holding duration and temperature on the microstructure, retained austenite volume ratio and hardness. 8620H and 16MnCr5 grade camshafts were carburized at 925 • C in endogas atmosphere (20% CO, 40% N2, 40% H2) for 1440 min. At the end of carburing process the diffusion temperature was decreased to 840 • C, which is the austenizing temperature, and he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…Various research groups have also reported extensive RA transformation during cryogenic treatment for carburised steels (see the overview of investigated steels in Table 1). Furthermore, these results are mostly consistent with the abovementioned general tendency; the use of −196 • C (or a lower temperature, combined with sequence A) is much more effective than the use of CT temperatures in the range from −70 to −120 • C [33,180,[225][226][227][228].…”
Section: Carburised Steelssupporting
confidence: 87%
See 3 more Smart Citations
“…Various research groups have also reported extensive RA transformation during cryogenic treatment for carburised steels (see the overview of investigated steels in Table 1). Furthermore, these results are mostly consistent with the abovementioned general tendency; the use of −196 • C (or a lower temperature, combined with sequence A) is much more effective than the use of CT temperatures in the range from −70 to −120 • C [33,180,[225][226][227][228].…”
Section: Carburised Steelssupporting
confidence: 87%
“…For steel subjected to CT at −196 °C for 24 h, this reduction was slightly higher (60%) [246]. In other work [228], Karaca et al reported that an application of −100 °C cryogenic treatment for 3.5 h improved wear performance by only 10%, but the treatment at −120 °C gave a 40% improvement in wear rate [234]. A CT duration of 24-36 h (at −185 or −196 °C) was recommended as optimal to achieve the best wear performance of bearing steels [24,151,244].…”
Section: Ball Bearing Steelsmentioning
confidence: 61%
See 2 more Smart Citations